2021
DOI: 10.3390/su13073976
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Scientific Research as a Sustainable Development Goal in Spanish Public Universities

Abstract: One of the Sustainable Development Goals for 2030 is building resilient infrastructure, promoting inclusive and sustainable industrialisation, and fostering innovation. This paper aims to analyse the possible consequences of stimulating commercial exploitation of academic research, encouraged by recent policy initiatives and legislative changes, on the quantity and quality of scientific knowledge in Spain’s public universities. We collected data of innovation variables (national patents, R&D and consultanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In recent years, the audit of colleges and universities has found that the construction of discipline cultivation is not in place, the effectiveness of scientific research results in serving industrial development is low, the use of some funds is not standardized, and the utilization rate of some large-scale instruments and equipment is not high, which restricts the connotative and high-quality development of colleges and universities and urgently requires the strengthening of financial and accounting supervision. With the progress and wide application of big data, artificial intelligence, and other technologies, the information system platform of university accounting supervision has the conditions to be organically connected and share resources with other business systems, external industrial and commercial systems, tax systems, etc., so that it becomes possible to build a new model of intelligent accounting supervision based on information sharing, real-time supervision, and whole-process supervision [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the audit of colleges and universities has found that the construction of discipline cultivation is not in place, the effectiveness of scientific research results in serving industrial development is low, the use of some funds is not standardized, and the utilization rate of some large-scale instruments and equipment is not high, which restricts the connotative and high-quality development of colleges and universities and urgently requires the strengthening of financial and accounting supervision. With the progress and wide application of big data, artificial intelligence, and other technologies, the information system platform of university accounting supervision has the conditions to be organically connected and share resources with other business systems, external industrial and commercial systems, tax systems, etc., so that it becomes possible to build a new model of intelligent accounting supervision based on information sharing, real-time supervision, and whole-process supervision [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific and technological innovation and scientific and technological management are complementary and inseparable. Changing the university research management mechanism is conducive to improving the quality and performance of scientific research activities and enhancing the output benefits of university knowledge results [11]. Literature [12] established an index system with R&D investment, technological innovation, and economic growth as the research variables and carried out an empirical analysis, pointing out that all the above three factors have stagnated and slowly declined, and it is necessary to continue to improve the incentive mechanism for scientific and technological innovation, improve the efficiency of capital investment and research and development, and at the same time, accelerate the marketing of the results of innovation.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many studies deal with the issue of sustainability from different perspectives, but only a few studies deal with the measurement of enterprise sustainability. The existing studies analyze the measurement of sustainability primarily at the macro level, i.e., for countries, regions, cities or industries [3][4][5][6][7][8][9], rather than at the micro level, focusing on an enterprise approach. From a micro perspective, few studies directly examine the application of sustainability practices and their performance evaluation [10].…”
Section: Introductionmentioning
confidence: 99%